H0LiCOW XII. Lens mass model of WFI2033 − 4723 and blind measurement of its time-delay distance and H0. Issue 1 (16th September 2019) - Rusu, Cristian E; Wong, Kenneth C; Bonvin, Vivien; Sluse, Dominique; Suyu, Sherry H; Fassnacht, Christopher D; Chan, James H H; Hilbert, Stefan; Auger, Matthew W; Sonnenfeld, Alessandro; Birrer, Simon; Courbin, Frederic; et al.
ABSTRACT: We present the lens mass model of the quadruply-imaged gravitationally lensed quasar WFI2033 − 4723, and perform a blind cosmographical analysis based on this system. Our analysis combines (1) time-delay measurements from 14 yr of data obtained by the COSmological MOnitoring of GRAvItational Lenses (COSMOGRAIL) collaboration, (2) high-resolution Hubble Space Telescope imaging, (3) a measurement of the velocity dispersion of the lens galaxy based on ESO-MUSE data, and (4) multi-band, wide-field imaging and spectroscopy characterizing the lens environment. We account for all known sources of systematics, including the influence of nearby perturbers and complex line-of-sight structure, as well as the parametrization of the light and mass profiles of the lensing galaxy. After unblinding, we determine the effective time-delay distance to be 4784_-248^+399 Mpc, an average precision of 6.6 per cent . This translates to a Hubble constant H_0 = 71.6_-4.9^+3.8 km s^-1 Mpc^-1, assuming a flat ΛCDM cosmology with a uniform prior on Ωm in the range [0.05, 0.5]. This work is part of the H 0 Lenses in COSMOGRAIL's Wellspring (H0LiCOW) collaboration, and the full time-delay cosmography results from a total of six strongly lensed systems are presented in a companion paper (H0LiCOW XIII).